EFEITOS DE DENÚNCIA DE ASSÉDIO SEXUAL EM AMBIENTE DIGITAL: UMA ANÁLISE DISCURSIVA - AFONSO, Edilene Rodrigues (2023)
This research is carried out in the materialist theoretical-methodological perspective of Discourse Analysis, mobilizing mainly the categories of discursive memory, denunciation, cynicism and discursive place, as theoretical contribution the authors Pêcheux (2014 [1975]; 1999 [1983]), Orlandi (2015; 2007; 2001), and Indursky (2011). And for the discussion of gender and race, we bring as theoretical contribution the following authors: França (2013; 2016; 2017; 2018;), Chaves (2013; 2015), Cestari (2015; 2017), Vergès (2020), and Gonzalez (1983). We constitute an archive from materialities formulated and put into circulation in the digital environment, published between 2015 and 2021. They are screenshots of private conversations, formulated in the social networks Facebook and Twitter, and published in the news portals R7, G1, OCPNews, Portal da Cidade Brumadinho, on the Canaltech website and also on Twitter, comments on the publications, reports on #Exposed and laws in which virtual sexual harassment can be framed. The discourses of the subjects in the position of harassers and harassed that are present in the screenshots constitute the corpus of this research, whose guiding questions refer to analyze which effects of meaning are circulating through the memory present in the interdiscourse of the SDs, in the discourse of cyberharassment in the digital environment. To carry out this discourse analysis we ask: what are the meanings of being a woman and being a man that can be analyzed in the discourses of subjects, whose conditions of production are manifested in the digital space? Therefore, the research aims to analyze what senses of harassment, of being a woman and being a man are put into circulation from the discourses of male individuals, in situations considered sexual harassment in the digital environment. We realized, at the end of the analyses, that the digital environment has a primary role both in the gestures of anonymous denunciations made by women in the position of being harassed, and in the exposure and more violence that also happens in this space, because sexual harassment has persisted in society for ages, and the way it occurs has expanded to other spaces, contributing to the formation of discursive spaces that consolidate the confrontation of harassment.